A Study of Occupational Stress among Teacher Educators in Relation to Gender and Position - et.al, Mr.R.Senthil kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of education has been widely recognized in today's information culture. In all developing countries devote a significant portion of their budget to education. More investment in education is intended because it is the only industry that reimburses more than it yields. This compensation could come in the form of new inventions or facilities. Teachers play an important role in the educational system of many countries because the success of educational institutions is typically contingent on teachers, who educate the nation's most valuable assets, including college students. As a result, teacher success is a critical concern for all educational institutions. Different stress contributing factors that occur either within or outside of the academic institution, that obstruct the performance of teachers, resulting in a decrease in individual as well as institutional productivity, negatively encourage the teacher's overall performance.